Non‐Oxidative Dehydrogenation Pathways for the Conversion of C2–C4 Alcohols to Carbonyl Compounds. Issue 23 (24th November 2015) - Shylesh, Sankaranarayanapillai; Kim, Daeyoup; Ho, Christopher R.; Johnson, Gregory R.; Wu, Jason; Bell, Alexis T.
Abstract: Invited for this month′s cover is the group of Alexis T. Bell at The University of California, Berkeley in Berkeley, California. The image shows the utility of gold nanoparticles deposited on hydrotalcite (Au/HT) for the continuous gas‐phase non‐ oxidative dehydrogenation reaction of bioderived C2 –C4 alcohols to the respective carbonyl compounds and hydrogen. The Communication itself is available at10.1002/cssc.201500786 . Abstract : "Producing carbonyl compounds from bio‐derived alcohols is a topic of considerable interest…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201500786 . View the Front Cover here:10.1002/cssc.201501451 .